THE IMPACT OF THE LIQUIDATION OF THE QUASI-JUDICIAL INSTITUTION OF THE CONSUMER DISPUTE RESOLUTION BODY ON CONSUMERS’ ACCESS TO JUSTICE AND ITS REORGANISATION EFFORTS FROM THE PERSPECTIVE OF SIYASAH SYAR’IYAH - Jannani, Nur; Yasin, Noer; Musataklima, Musataklima (Jurisdictie: Jurnal Hukum dan Syariah, 2024)
The Consumer Dispute Settlement Body (BPSK) is authorised to settle consumer disputes located at the district and/or city level. However, following the enactment of Law No. 23/2014 on Local Government (Local Government Law), BPSK was dissolved and transferred to the provincial level. This study aims to determine the causes of BPSK dissolution, its impact on access to justice for consumers and its reorganisation efforts so that it contributes to consumer protection. The research is empirical legal research with a sociological juridical approach. The primary and secondary data were analysed prescriptively. The research results show that the transformation of management and authority to form BPSK from district and/or city governments to provinces by the Regional Government Law resulted in the existence of BPSK in districts and/or cities having to be liquidated. This has implications for limited consumer access to obtain justice. The recommendation from this research is that the government needs to reorganise the legal position of BPSK by returning BPSK's position to districts and/or cities. This can be achieved through legal politics based on siyasah syar'iyah. This article can be a basic reference for the development of consumer dispute resolution institutions based on consumer protection.Badan Penyelesaian Sengketa Konsumen (BPSK) adalah lembaga yang berwenang menyelesaikan sengketa konsumen yang berada di tingkat kabupaten dan/atau kota. Namun setelah disahkannya Undang-Undang Nomor 23 Tahun 2014 tentang Pemerintahan Daerah (UU Pemerintahan Daerah), BPSK dibubarkan dan dipindahkan ke tingkat provinsi. Penelitian ini bertujuan untuk mengetahui penyebab pembubaran BPSK, dampaknya terhadap akses keadilan bagi konsumen dan upaya reorganisasinya sehingga berkontribusi terhadap perlindungan konsumen. Penelitian ini merupakan penelitian hukum empiris dengan pendekatan yuridis sosiologis. Data yang digunakan adalah data primer dan sekunder yang dianalisis secara preskriptif. Hasil penelitian menunjukkan bahwa peralihan kepengurusan dan kewenangan pembentukan BPSK dari pemerintah kabupaten dan/atau kota kepada provinsi berdasarkan Undang-Undang Pemerintahan Daerah mengakibatkan keberadaan BPSK di kabupaten dan/atau kota harus dilikuidasi. Hal ini berimplikasi pada terbatasnya akses konsumen untuk memperoleh keadilan. Rekomendasi dari penelitian ini adalah pemerintah perlu menata kembali kedudukan hukum BPSK dengan mengembalikan kedudukan BPSK kepada kabupaten dan/atau kota. Hal ini dapat dicapai melalui politik hukum berdasarkan siyasah syar'iyah. Artikel ini dapat menjadi acuan dasar bagi pengembangan lembaga penyelesaian sengketa konsumen yang berbasis perlindungan konsumen.